Differences in Food and Beverage Marketing Policies and Practices in US School Districts, by Demographic Characteristics of School Districts, 2012 - Merlo, Caitlin L. (Prev Chronic Dis, 2016)
INTRODUCTION: Foods and beverages marketed in schools are typically of poor nutritional value. School districts may adopt policies and practices to restrict marketing of unhealthful foods and to promote healthful choices. Students’ exposure to marketing practices differ by school demographics, but these differences have not yet been examined by district characteristics. METHODS: We analyzed data from the 2012 School Health Policies and Practices Study to examine how food and beverage marketing and promotion policies and practices varied by district characteristics such as metropolitan status, size, and percentage of non-Hispanic white students. RESULTS: Most practices varied significantly by district size: a higher percentage of large districts than small or medium-sized districts restricted marketing of unhealthful foods and promoted healthful options. Compared with districts whose student populations were majority (>50%) non-Hispanic white, a higher percentage of districts whose student populations were minority non-Hispanic white (≤50% non-Hispanic white) prohibited advertising of soft drinks in school buildings and on school grounds, made school meal menus available to students, and provided families with information on school nutrition programs. Compared with suburban and rural districts, a higher percentage of urban districts prohibited the sale of soft drinks on school grounds and used several practices to promote healthful options. CONCLUSION: Preliminary findings showing significant associations between district demographics and marketing policies and practices can be used to help states direct resources, training, and technical assistance to address food and beverage marketing and promotion to districts most in need of improvement.